Contemporary analysis of maternal and neonatal morbidity after uterine rupture: A nationwide population‐based study. Issue 5 (11th February 2017) - Vilchez, Gustavo; Dai, Jing; Kumar, Komal; Lagos, Moraima; Sokol, Robert J.
Abstract: Aim: Uterine rupture is a rare but feared perinatal event. Despite abundant research and changes to guidelines implemented to reduce this complication, evaluation of whether uterine rupture still engenders significant maternal/neonatal morbidity has not been conducted. We analyzed recent cases of maternal/neonatal morbidity after uterine rupture. Methods: Deliveries complicated by uterine rupture from 2011 to 2012 in the United States were selected. Comparison cases without uterine rupture were used as controls. Measures of maternal/neonatal complications were compared with χ 2 test, and relative risks were calculated. Logistic regression was used to identify the most significant complications. P < 0.05 indicated statistical significance. Results: From 7 922 016 births, 1925 cases of uterine rupture and 3765 controls were identified. Regression models retained four maternal outcomes; blood transfusion was the most common ( 15%) and unplanned hysterectomy had the highest odds ( 97‐fold). For newborns, the model retained three measures of morbidity; neonatal intensive care unit admission was the most common ( 35%) and seizures had the highest odds ( 20‐fold). Conclusions: Despite efforts to reduce complications, mothers remain at significant risk of unplanned hysterectomy and intensive care unit admission. Neonates are at sizeable risk for neonatal intensive care unit admission and seizures, recognized markers of long‐term neurobehavioral abnormality. Uterine rupture remains a major risk for mothers and babies.